Wzorzec tekstowy przysięgi sądowej ("iuramentum promissorium") w XVI wieku = Text pattern of a judicial oath ("iuramentum promissorium") in the 16th century - Kość, Józef (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Bartłomiej Groicki, as the first Polish lawyer-practitioner, presented in a 1559 book, "Porządek sądów I spraw miejskich prawa majdeburskiego w Koronie Polskiej", a promissory oath in a comprehensive approach, i.e. both as a model oath formula (rota), which used to be taken by court clerks before they began their procedural activities, and as a ceremonial activity carried out in an official institution in accordance with a traditional and, already then, solemn ritual .
Keywords: przysięga promissoryjna; wzrorzec tekstowy; akt mowy; struktura tekstu; prawo magdeburskie; promissory oath; text pattern; speach act; text structure; Magdeburg Law